Application of the Theory of Planned Behavior to Predict Drug Abuse Related Behaviors - sayed said Mazloomy MahmoodAbad; Khair Mohammad Jadgal; Ehsan Movahed (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Drug abuse among adolescents potentially holds several negative consequences for the health and well-being of the youth. This theoretically based study explained predictability of the Theory of Planned Behavior (TPB) on drug abuse related behaviors among adolescents. Methods: This descriptive study was conducted in Yazd City, Iran, in 2015 among 125 male adolescents in the age range of 11 - 29 years, recruited randomly. All data gathered by using self-report written questionnaires included attitudes, subjective norms, perceived behavioral control, intention not to use drugs as theoretical constructs of TPB, and drug abuse related behaviors. Results: The results showed that 18 % of participants were smoker, 97 % of them did not have history of synthetic drug abuse by parents, and 6 % of participants reported synthetic drug abuse by friends. Results of Chi-square test showed that there was a significant relationship between smoking and father's education, family size, history of synthetic drugs in parents, history of synthetic drugs in friends, and participants' job (P ˃ 0.000). However, maternal education (P = 682) and living with parents (P = 729) did not have any significant relationship. Conclusions: The low prevalence of Drug abuse in this study in comparison with the existing statistics can attribute to lack of participants' reports.